Solar irradiance forecasting model using Artificial Neural Network (ANN): article - Zahare, Syazwani; Sulaiman, Shahril Irwan (2014)
This paper presents the Artificial Neural Network (ANN) model for predicting solar irradiance. The inputs of the ANN are the solar irradiance values for previous five one-minute intervals while the output of the ANN is the solar irradiance of the sixth-minute interval. The solar irradiance data were obtained from a weather monitoring station at Green Energy Research Centre (GERC) at Universiti Teknologi MARA, Malaysia. During testing, the ANN produced a low mean absolute percentage error (MAPE) of 10.5796% and high coefficient of determination, R2 of 0.8925.